GLP−1 receptor agonists for the treatment of obesity: Role as a promising approach - Wang, Jing-Yue; Wang, Quan-Wei; Yang, Xin-Yu; Yang, Wei; Li, Dong-Rui; Jin, Jing-Yu; Zhang, Hui-Cong; Zhang, Xian-Feng (Frontiers in Endocrinology, 2023)
Obesity is a complex disease, excessive fat accumulation caused by genetic, environmental and other factors, that has seen the most rapid growth in terms of morbidity and mortality in recent years, posing the biggest threat to people's health and lives and increasing public health care expenses. Many shreds of evidence show that weight loss can significantly reduce the risk of obesity-related complications and chronic diseases. Diet control, moderate exercise, surgery and drug treatment have made it possible to lose weight. However, given the safety or effectiveness of these drugs, the current drugs that need to lose weight have limitations in clinical use. Glucagon-like peptide -1 receptor (GLP-1R) agonists are a group of drugs based on incretin, receptors of which are widely distributed in nerves, islets, heart, lung, skin and other organs. More and more trials have proved its effectiveness and safety in treating or preventing obesity. Therefore, GLP-1R agonist is a new and promising choice for obese individuals. In this review, it describes the evidence of research into GLP-1R agonists for obesity treatment from the animals' or humans’ perspective. We anticipate that this study will help biomedical researchers use GLP-1R agonists to treat obesity by providing more and novel drug strategies or scientific research ideas.